Controlling Shareholder And Firm Value: An Empirical Study On Malaysian Public Listed Companies - Hooy, Guat Khim (2013)
Previous studies on corporate ownership and firm value relationship focused much on board ownership or direct ownership. The examination on the relationship based on ultimate ownership of the largest shareholder is still limited, especially in a developing country like Malaysia. This study seeks to contribute to the existing literature by examining the relationship from the perspective of ultimate ownership. The use of ultimate ownership which covers direct and indirect shareholdings should be more appropriate as majority of the publicly listed firms in Malaysia are under the control of dominant shareholders and a number of the firms are owned by the ultimate owner through indirect shareholdings by a chain or several chains of firms. From the standpoint of ultimate ownership, this study analyzed the effects of controlling shareholder on firm value for several areas of corporate ownership structure. Using the method of panel data regression, 295 firms listed on the Main Board of Bursa Malaysia covering the period from 2001 to 2009 were examined. The findings support that presence of controlling shareholder contributes to better firm value. This indicates that their existence is competent in mitigating the agency problem in dispersed ownership firm. It suggests that the development of the rules and regulations should also protect the incentives of the controlling party as their presence is important to the growth of the firm. The results for control mechanisms reveal that controlling shareholder is more likely to expropriate corporate assets through multiple control chains than pyramidal structure. The next findings reflect that involvement in management by the controlling shareholder is detrimental to firm value. Further test shows that their managerial ownership is non-linearly related to firm value. This implies that different set of guidelines or rules could be introduced at different levels of managerial ownership in order to minimize the negative impact of managerial ownership of the controlling shareholder. In terms of ownership identity, the results indicate that the government and foreign controlling shareholder have positive impact on firm value. Besides that, foreign controlled firms outperform other types of firms. Finally, the results show that the adverse effect of involvement in management and control mechanisms are more pronounce for foreign firms. It seems that the advantages of foreign controlled firms such as managerial expertise are no longer effective in mitigating the agency problems. In contrast, it in turn becomes the factors that encourage the controlling shareholder to extract private benefits.